Simulation study of UWB interference effects on GSM 900 system - Abdullah A.; Ahmad A.; Sauti M.S.; Erana Y.; Shaaya S.A.; Mustafa I.S. (2023)
The impact of UWB interference on GSM 900 was studied in view of Federal Communication Commission (FCC) regulations. The maximum UWB transmitter power levels that would cause ldB performance degradation on GSM 900 receivers were determined. UWB densities were computed for different GSM cluster size and the results showed that there is no harmful interference for GSM 900 system. 2008 IEEE.